आदिवासी ठाकर (समाजशास्त्रीय अध्ययन) - (:unkn) unknown (Abhyasika Prakashan Aurangabad Maharashtra, 2010)
Aadiwasi Thakar is a Sociological Study writen in Marathi.
Aadiwasi Thakar (Sociological Study)
Keywords: Marathi; Tribal Studies; Marathi; Marathi